Implementation Discovery Learning Model in Arabic Free Writing - Farida Fauziah; Saefudin Saefudin; Amin Al Masyhuri; Muhammad Ilyas Alkayisy (UIN Sunan Gunung Djati Bandung, 2025)
Arabic writing skills are essential for comprehensive language mastery. However, teaching free writing often faces challenges, including less engaging methods and learning models. This research aims to identify effective learning models, key elements, and obstacles encountered in teaching Arabic free writing skills. Free writing is the culminating stage in developing Arabic writing skills, encompassing expressing thoughts and feelings using appropriate vocabulary and grammar. Employing a qualitative approach with descriptive and analytical designs, data is collected through interviews, observations, and document analysis. The results reveal that the applied learning model is structured from objective setting to evaluation, focusing on students' ability to write grammatically correct sentences. Learning material, themed